Guidantonio Arcimboldi orator for the Sforzas in Hungary and the lost frescoes of the Bicocca (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
The fifteenth-century suburban villa known as Bicocca degli Arcimboldi (now located in the homonymous neighborhood in Milan) still retains in the portico a fragment of a lost painted cycle depicting a diplomatic mission lead by owner and future archbishop Guidantonio Arcimboldi to Hungary in 1488. This paper aims to shed light on the events that inspired the paintings and investigate the possible reasons behind the choice of the subject, while analyzing how such themes were represented in two well-known contemporary examples.
Keywords: Diplomacy; 15th century; Guidantonio Arcimboldi; Hungary; Bicocca; Frescoes